Bedrock-Hosted Diffusive Hot Storage for Large-Scale Thermo-Electric Energy Storage by Thermal Doublet. (2017) - Nguyen, D.; Macchi, E.G.; Colin, C.; Tauveron, N.; Tartière, T.
Abstract: Superficial unfractured dry crystalline bedrock (e.g. granite) can constitute the diffusive hot storage for a large-scale thermo-electric energy storage by thermal doublet, an ice storage being the latent cold sink of the thermal doublet and supercritical CO2 (sCO2 ) the heat transfer working fluid circulating inside closed-loop vertical geothermal exchangers. Operative 30 °C–140 °C thermal range of the diffusive hot storage will not alter mechanical resistance or thermal conductivity of the encasing bedrock. Technological issue for thermal coupling of the geothermal exchanger with the bedrock at working fluid temperatures above 100 °C is solved by coaxial exchanger design implementing silicone rubber as wall material. Difficulties of modeling heat transfer for the full-scale geothermal exchanger due to Reynolds number up to 10 6 for the flow regime inside the exchanger are addressed through a simplified modeling approach. Experimental investigation on 1/10 scale heat exchanger prototype with sCO2 as working fluid is conducted to study heat transfer performance and storage dynamics, and also to validate the full-scale modeling.